2020
DOI: 10.2337/db19-0996
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell–Specific Deletion of HMG-CoA (3-hydroxy-3-methylglutaryl-coenzyme A) Reductase Causes Overt Diabetes due to Reduction of β-Cell Mass and Impaired Insulin Secretion

Abstract: Inhibitors of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), statins, which are used to prevent cardiovascular diseases, are associated with a modest increase in the risk of new-onset diabetes. To investigate the role of HMGCR in the development of β-cells and glucose homeostasis, we deleted Hmgcr in a β-cell–specific manner by using the Cre-loxP technique. Mice lacking Hmgcr in β-cells (β-KO) exhibited hypoinsulinemic hyperglycemia as early as postnatal day 9 (P9) due to decreases in both β-cell mass and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…In our results ( Figure 5 B and Table S6 ), eleven (phospho)proteins (HMGCR, IRS2-T517, T524, PCLO-S4823, SYTL4-S217, BAIAP3-S215, RAB3B, ABCA1-S2234, CLASP1-S1220, CADM1, SCG2-S534, and CHGB-S79,S397,T400,S405) were involved in insulin secretion, and they were restored towards normal in DMT1 -silenced β-cells against IL-1β exposure. For instance, β-cell-specific silencing of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) acutely triggered the reduction of β-cell mass and insulin secretion after postnatal day 9 in mice and eventually leading to the development of diabetes [ 97 ]. Knock-down of cell adhesion molecule 1 (CADM1) promotes GSIS in rat and human islet β-cells whereas the induction of CADM1 inhibits GSIS [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our results ( Figure 5 B and Table S6 ), eleven (phospho)proteins (HMGCR, IRS2-T517, T524, PCLO-S4823, SYTL4-S217, BAIAP3-S215, RAB3B, ABCA1-S2234, CLASP1-S1220, CADM1, SCG2-S534, and CHGB-S79,S397,T400,S405) were involved in insulin secretion, and they were restored towards normal in DMT1 -silenced β-cells against IL-1β exposure. For instance, β-cell-specific silencing of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) acutely triggered the reduction of β-cell mass and insulin secretion after postnatal day 9 in mice and eventually leading to the development of diabetes [ 97 ]. Knock-down of cell adhesion molecule 1 (CADM1) promotes GSIS in rat and human islet β-cells whereas the induction of CADM1 inhibits GSIS [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Statin-induced reduction in insulin secretion from β-cells happens because statins disrupt the production of endogenous cholesterol in β-cells, which is important to maintain the functionality of CaV channels and insulin secretion [ 17 ]. Additionally, pancreatic β-cell-specific ablation of HMGCR gene in mice resulted in a phenotype with severe hypoinsulinemia and hyperglycemia [ 43 ]. This study revealed the importance of HMGCR and mevalonate pathway for pancreatic β-cell development [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pancreatic β-cell-specific ablation of HMGCR gene in mice resulted in a phenotype with severe hypoinsulinemia and hyperglycemia [ 43 ]. This study revealed the importance of HMGCR and mevalonate pathway for pancreatic β-cell development [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After female mice were acclimated in an individual metabolic cage for 3 days, VO2 and VCO2 were measured using ARCO-2000 (ARCO System) for 4 days as described previously (49). Locomotor activity was measured using the ACTIMO-100 activity monitoring system (Shinfactory).…”
Section: Locomotor Activity and Indirect Calorimetrymentioning
confidence: 99%